A little bit of Sargassum goes a long way: seafloor observations of Sargassum fluitans and Sargassum natans in the Western Atlantic Ocean - Pries, Ashley; Netburn, Amanda N.; Batchelor, Heidi; Hermanson, Victoria R. (Frontiers in Marine Science, 2023)
The North Atlantic Ocean features high seasonal productivity of the brown seaweed Sargassum, which floats on the ocean surface and accumulates in large numbers in the Sargasso Sea. Sargassum blooms can stretch from the west coast of Africa to the Gulf of Mexico, and have created the largest seaweed blooms ever observed. Sargassum blooms have increased in intensity in recent years, and can negatively impact coastal communities when they wash up onshore in large quantities and decay. While seaweed sinking from surface waters to the seafloor may be an important carbon sink by removing carbon from the atmosphere, the magnitude of carbon sequestration by Sargassum and other macroalgae remains poorly understood. Given the magnitude of Sargassum blooms in the North Atlantic, they may pose a significant mechanism for carbon sequestration in the deep sea, though direct observations are rare. In this study, we documented the presence and distribution of Sargassum seaweed on the seafloor using video from ten remotely operated vehicle dives conducted on NOAA Ship Okeanos Explorer. Locations included sites in the Gulf of Mexico, in the Caribbean Sea, and off the Southeastern United States. Sargassum was observed in numbers ranging from 0 to over 112 per dive, and a frequency of between 0-11.23 observations for every 100 meters of horizontal distance. These observations suggest that Sargassum does make its way to the deep sea in potentially significant amounts. Natural systems like Sargassum sinking could serve as natural laboratories for understanding and managing seaweed burial as a climate mitigation strategy. Long-term monitoring of the fate of sunken Sargassum on the seabed is needed in order to determine how much is ultimately sequestered rather than recycled back into the system. Such observations would inform the feasibility of Sargassum farming and/or facilitated sinking as potential carbon dioxide removal strategies.